PELATIHAN PENGOPERASIAN PLATFORM PEMBELAJARAN ONLINE DALAM MASA PANDEMI COVID-19 BAGI ANAK-ANAK DESA BATUAJI KECAMATAN RINGINREJO KABUPATEN KEDIRI - Riska Aprilia; Tri Damayanti Intan; Ninik Yustina Sari; Lifa Rosiana Putri (Jurnal Praksis dan Dedikasi Sosial (JPDS), 2023)
TRAINING OF ONLINE LEARNING PLATFORM OPERATIONAL PROCEDURE FOR CHILDREN IN BATUAJI, KEDIRI, DURING THE COVID-19 PANDEMICOnline learning is commonly carried out. Especially during the COVID-19 pandemic, online learning is implemented to prevent the extensive spread of COVID-19. However, during its implementation, online learning faces a number of hindrances, such as the student’s inability to operate the online learning platform, which reflects the unpreparedness for online learning. Therefore, we conducted training on online learning platform operations for children from Batuaji, Kediri, Indonesia. This training aimed to help students operate a number of online learning platforms, such as  google classroom, zoom, google meet, edmodo, quizizzz, and whatsapp. The elementary school and junior high school-age children participated in this training. The training process was initiated by introduction, short material delivery related to the online learning platforms, quizzes, and evaluation. This training is helpful for the participants, as reflected by their great enthusiasm during the training activities and great understanding of online learning platforms’ operation procedures after attending the training.Pembelajaran online merupakan kegiatan yang sedang dilaksanakan selama pandemi COVID-19. Hal ini dilakukan guna menghindari penyebaran COVID-19 yang semakin meluas. Sesuai dengan praktiknya kegiatan pembelajaran online menemui beberapa hambatan, salah satunya yakni banyaknya anak-anak yang belum menguasai penggunaan platform pembelajaran online sehingga menimbulkan ketidaksiapan dalam pembelajaran online. Oleh karena itu, kegiatan ini bertujuan untuk memberikan solusi dengan mengadakan pelatihan pengoperasian platform pembelajaran online dalam masa pandemi COVID-19 bagi anak-anak di Desa Batuaji Kecamatan Ringinrejo Kabupaten Kediri guna membantu agar mereka memahami cara mengoperasikan beberapa platform pembelajaran online seperti google classroom, zoom, google meet, edmodo, quizizz dan whatsapp. Pelatihan ini dilakukan bagi anak-anak SD dan SMP dengan rangkaian kegiatannya diawali perkenalan, pemaparan materi tentang platform pembelajaran online secara singkat, praktik kuis, dan evaluasi pelatihan. Hasil pelatihan ini sangat bermanfaat, bahkan semua peserta pelatihan sangat antusias selama kegiatan berlangsung serta mereka juga memahami beberapa aplikasi yang baru mereka kenal selama pelatihan.